Superplasticizer's efficiency on the mechanical properties of recycled aggregates concrete: Influence of recycled aggregates composition and incorporation ratio. (30th October 2017) - Bravo, M.; de Brito, J.; Evangelista, L.; Pacheco, J.
Highlights: Four different untreated CDW sources. Influence of CDW composition on the performance of polycarboxylic superplasticizers. Superplasticizer effect on workability, compressive and tensile strengths, and Young's modulus. Recycled aggregate characteristics limit the efficiency of superplasticizers. Superplasticizers lose efficiency when used with CDW aggregates instead of concrete waste. Abstract: Most research on recycled aggregates concrete concern aggregates produced from concrete waste, rather than actual construction and demolition waste. Different investigations have assessed that sulfonated-based superplastizers are not as efficient in recycled aggregates concrete than on natural aggregates concrete, but no significant loss of polycarboxylic-based superplasticizer efficiency has been reported. This may not be valid when the aggregates are sourced from actual construction and demolition waste, due to the higher porosity, roughness, and weaker mechanical properties of aggregates produced from this source. This paper analyses the mechanical properties of superplasticized concrete with the incorporation of construction and demolition waste. Recycled aggregates produced from construction and demolition waste were taken directly from plants and used as aggregates without screening or treatment, emulating what would happen in a practical application by the concrete industry. The results of the tests and the superplasticizer's efficiency are compared with results on natural aggregate concrete compositions and on analogue recycled concrete aggregate concrete compositions with and without superplasticizers. The composition of the different construction and demolition waste aggregates is considered during the analysis of results. Evidence was found that when recycled aggregates are sourced from construction and demolition waste, polycarboxylic-based superplasticizers perform satisfactorily but may not be as efficient as in natural aggregate concrete compositions.